ORGANIZATIONAL CITIZENSHIP BEHAVIORS: analysis of the phenomenon in a micro-enterprise - Teixeira, Edivan Dos Santos Gomes; Failli, Gabrieli Moreno; Pianno, Rafael Francisco Campos (Revista Interface Tecnológica, 2025)
This work aims to identify the level of organizational citizenship among an organization’s employees. After studies were carried out, the importance of members who adhere to good practices on the topic was confirmed. Factors that affected these values were analyzed, being beneficial in a corporate environment and how they affected the relationship with superiors. A survey revealed team characteristics and organizational citizenship factors that generate job satisfaction. The results highlighted employees’ support for the company’s image and cooperation between them, demonstrating a good relationship. However, problems were identified, such as members’ lack of habit of expressing their ideas, indicating that improvements should be renewed. The study concludes that clear and direct communication, allowing the expression of ideas, is essential for the team’s success and the company’s growth.